Effect of environmental characteristics on the diversity of aquatic macroinvertebrates in Andean rivers regulated for hydroelectric generation - Ríos-Pulgarín, María Isabel; Giraldo-Sánchez, Carlos Eduardo; Calvo-Cardona, Samir Julián; Londoño Valencia, James (Revista de Biología Tropical, 2022)
Introduction: The Andes are characterized by an abundance of water resources and flows are frequently regulated by reservoirs for the generation of energy. The effects of regulation on aquatic macroinvertebrate communities are not well known in Colombia. Objective: To test the hypothesis that regulated currents have less macroinvertebrate diversity. Methods: We collected water and organism samples before, and after, the regulation of the Tafetanes, Calderas and Arenosa rivers, in Antioquia, Colombia, during various hydrological cycles (rain, transition and drought) and climatic phenomena (ENSO/El Niño Phenomenon) between 2016 and 2018. Results: We collected 53 214 individuals, from 165 taxa, mostly from the orders Ephemeroptera, Plecoptera, Trichoptera and Diptera (90 % of captures). Changes in diversity responded to spatial differences rather than to physicochemical variables: diversity was higher in non-regulated sites, regardless of the hydrological period or associated ENSO. Most species were found in all sampling sites, but abundance was higher in the site with the best habitat conservation status. Conclusion: The results support the hypothesis that physical barriers have effects on macroinvertebrate diversity at the local scale, however, the condition of adjacent habitats also seems to play an important role in preserving richness and abundance. The conservation of forest adjacent to the riverbed could mitigate the impacts of regulation.